Notes on the circumscription of Pterygota (Malvaceae, Sterculioideae) with special reference to a Brazilian taxon with a misapplied name - Colli-Silva, Matheus; Pirani, José Rubens (Phytotaxa, 2019)
Pending taxonomic problems regarding Pterygota Schott & Endl. are related to troublesome circumscription and historical-nomenclatural issues. For instance, Pterygota brasiliensis Allemão is cited as Basiloxylon brasiliensis (Allemão) K.Schum in some publications, e.g. the Catalog of Plants and Fungi of Brazil (Forzza et al. 2010) and the Checklist of Vascular Plants of the Americas (Ulloa-Ulloa et al. 2017). Conversely, it is referred as P. brasiliensis in other works, such as the checklist of species from the Brazilian Atlantic Forest (Dutra et al. 2015) and now in the Brazilian Flora 2020 Project (Ferreira-Júnior 2018). Here, we review and standardize taxonomical issues regarding Pterygota, something which has not been addressed since the end of the 1960s, focusing on the Brazilian species P. brasiliensis.